PENGARUH KEPUASAN KERJA, IKLIM ORGANISASI, GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLA KEUANAGN DAN ASET DAERAH (BPKAD) KABUPATEN LABUHANBATU - Sirait, Wina Alya Febriana; Safri, Hayanuddin; Pohan, Muhammad Yasir Arafat (Universitas Wiralodra, 2025)
At the Regional Financial and Asset Management Agency (BPKAD) of Labuhanbatu Regency, this study aims to determine the influence of job satisfaction factors, organizational environment, leadership style, and work motivation on employee performance. Research on internal issues that have the potential to affect employee performance is very important to improve the efficiency of regional financial and asset management. This study was conducted involving 38 employees of the Regional Financial and Asset Management Agency (BPKAD) of Labuhanbatu Regency. For the purposes of this study, data were collected by distributing questionnaires to BPKAD employees working in Labuhanbatu Regency. Survey techniques and quantitative methodologies were used. A data analysis approach known as multiple linear regression was used to ensure that several variables had simultaneous and partial influences on each other. Employee performance was significantly and positively influenced by job satisfaction factors, organizational climate, leadership style, and work motivation, according to the results of the study. Employees who are satisfied with their jobs, who work in an organizational environment that supports their work, who are led by successful superiors, and who have a high drive to complete their tasks tend to show greater optimal performance. In addition, it has been proven that these four factors simultaneously have a significant impact on employee performance.